Auditoría de gestión al comité de crédito y cobranzas de la cooperativa de ahorro y crédito santa maría de la manga del cura Ltda. del cantón El Carmen, provincia de Manabí, año 2012 - Vera Vera, Delsi Elizabeth (2013)
The Performance Audit Department of Credit and Collections Cooperative Savings and Credit " Santa Maria de la Manga del Cura " Ltd. , is performed in order to describe the current situation of the lending process and evaluate the efficiency and effectiveness of the cooperative in implementing the activities proposed in the institutional arrangements in the period 2012. For the development of the research department information basically credit and collections, management and the Audit Committee was collected in order to assess the objectives and organizational strategies , the portfolio growth was analyzed for which a comparison was made of 2011 with 2012 , just as a study of the NPL ratio was performed , evaluating areas, the was performed using techniques such as observation, inspection and analysis, through the application of appropriate tools for conducting the audit. The end result of the audit work which identified weaknesses is basically not having the application of a regulation and manual credit and collections, but despite this weakness people who are at the forefront of the Cooperative try to do the best possible to carry out their activities. The findings with the application of the audit are evident in the final report has been prepared as a final product of labor.